ANALISIS PENERAPAN NILAI PENDIDIKAN KARAKTER PEDULI SOSIAL TERHADAP SIKAP KERJASAMA DAN GOTONG ROYONG PADA ORGANISASI SISWA INTRA SEKOLAH MADARASAH ALIYAH NEGERI 1 SURAKARTA TAHUN 2023/2024 - Wahyuni, Dian; TRISIANA, ANITA (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2024)
The aim of this thesis is 1 ) to find out about the application of the attitude of cooperation and mutual cooperation among OSIS members at MAN 1 Surakarta in 2023/2024 academic year, 2) to find out the level of effectiveness of the application of character education values regarding social care towards the attitude of cooperation and mutual cooperation to OSIS members. The results of the research could be conclude that 1) the management of OSIS MAN 1 Surakarta in 2023/2024 academic year could implement an attitude of cooperation and mutual cooperation well in all activities. Altough. There were several administrators who have not been able to Implement it well, 2) the implement of the attitude of cooperation and mutual cooperation among the members of OSIS MAN 1 Surakarta could be seen through the preparation and implementation of the Campus Expo activities which would be held on January 25-26 2024, 3) implementation the value of character education regarding social care had a high level of effectivitiveness in the attitude of cooperation and mutual cooperation, 4) in its implementation, there were parties who supported this social care character such as the deputy principal for curriculum, deputy principal for student affairs, OSIS supervisors, theachers, and OSIS administrators, 5) the attitude of cooperation and mutual cooperation that was expected of OSIS members was an attitude that could be carried out happily, comfortably, and they could carry out activities for the common goals of the organization. Keywords : Sosial Care Character, Implementation, OSIS